AN ANALYSIS OF IMPACT OF SOCIAL MEDIA MARKETING WITHIN THE FRAMEWORK OF CAUSE-BASED MARKETING - Modasiya, Soaeb Mohammed; Ambavale, Riddhi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Social media marketing is the utilization of social media technologies, channels, and software to create, communicate, deliver, and exchange offerings that have value for an organization’s stakeholder. Marketers and consumers are at present extending their communication through a dynamic new media called the social network. This is the latest development in advertising products and communicating with consumers. Social media is one of the fastest-growing, which encompasses enormous spontaneous brainstorming among its network members for developing an opinion . Actually, this robust social media platform has created an exemplary scope for any brand to advertise its product through exposure, attention and perception; to develop opinions; and to create values. The use of traditional one-way communication to promote consumer perception and boost favourable attitudes towards product value has been dramatically losing its persuasive influence due to the overarching appeal of Facebook as a method of connection for peers Now product judgement, evaluation and perception and the final attitude development processes have been drastically aligned with a new pattern of multidimensional communications where consumers are more interested in and find more credibility through pursuing and streamlining peered opinions instead of getting traditional marketing advertisements. Cause marketing creates a context for social activism by inducing pro social behaviour in consumers; however, not all consumers find every social issue relevant to their interests, values and goals. Marketers use messaging strategies to convey the importance of a social issue and make it seem relevant enough to motivate consumers to behave in a desirable way. In this era, social media platform can be integrated into the cause marketing strategy. This new technology sets out new mechanisms and communication tools that companies, governments and anyone who wants to engage in cause marketing can rely on to interact and engage with actual and potential customers.